Spring field reports, Eugene and Eloise Armstrong - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1994)
An annotated list of birds sighted by Eugene and Eloise Armstrong. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed